A white shark’s view: insights into the behaviour of a marine predator - Adrienne Gooden; Charlie Huveneers; Lucan Sinclair; Paul A. Butcher (Frontiers in Marine Science, 2026)
Animal-borne cameras are effective tools to study the fine-scale behavior and habitat use of a wide range of marine taxa, including birds, mammals, sea turtles, and elasmobranchs. We deployed animal-borne camera and accelerometer packages on 13 juvenile white sharks ( Carcharodon carcharias ; 174–283 cm total length) along the coast of New South Wales (Australia) to investigate white shark foraging behavior and habitat preferences. We annotated and assigned every second of footage to specific behaviors (e.g., swimming direction, foraging behavior) and environmental variables (e.g., habitat type) and recorded interactions with other species. From the 68.5 h of footage obtained, we identified 20 burst events (0.1% of the total time), but a potential prey was visible in only three of these instances (15% of burst events). Moreover, 10 of these burst events (50%) were along the seafloor without substantial changes in shark depth, potentially linked to benthic foraging behavior. White sharks mostly occupied sandy, low-complex habitats, which could be driven by prey availability, e.g., benthic elasmobranchs, or the ease of navigation compared to more complex environments. Our findings provide new insights into the foraging ecology and habitat use of juvenile white sharks and document novel interspecific interactions, highlighting the utility of animal-borne cameras in capturing behaviors that are otherwise difficult to observe.